Profiles of engagement in online communities of citizen science participation. (September 2017) - Aristeidou, Maria; Scanlon, Eileen; Sharples, Mike
Abstract: Citizen participation in online communities of scientific investigations has recently become more popular. Enhancing the engagement of citizens within these communities is a focus of attention for researchers and practitioners who want to amplify the impact on learning, science and society. This study investigates the relationship between engagement factors and behaviour patterns in an online community that requires high levels of citizen participation. While other studies explore engagement in communities where citizens contribute data, the current research investigates a community to support citizens in facilitating their own scientific investigations. Data were collected from log files and questionnaires, and multiple measures of engagement were examined: engagement metrics, roles, motivation, attitude, satisfaction and belonging to the community. The results allowed comparison of the engagement levels among different types of citizen participation communities and categorised members in engagement profiles, according to their behaviour patterns. Findings indicate a need for differing design approaches based on the type of citizen participation community and individual engagement profiles. Highlights: A study on engagement in a community of high levels of citizen participation. Engagement metrics and cluster analysis was used to classify behaviour patterns. Psychological engagement factors described the engagement profiles. Extrinsic factors attract/activate members, intrinsic factors sustain participation. More personalised design is needed depending on the type of community and members.